2019
DOI: 10.1029/2019wr025227
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeological Modeling and Water Resources Management: Improving the Link Between Data, Prediction, and Decision Making

Abstract: A risk-based decision-making mechanism capable of accounting for uncertainty regarding local conditions is crucial to water resources management, regulation, and policy making. Despite the great potential of hydrogeological models in supporting water resources decisions, challenges remain due to the many sources of uncertainty as well as making and communicating decisions mindful of this uncertainty. This paper presents a framework that utilizes statistical hypothesis testing and an integrated approach to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…The main objectives are to ensure that water resource systems are designed and managed to fully contribute to providing water of sufficient quantity and quality for agricultural, industrial, and municipal uses to meet the growing demands posed by social economic development, both now and in the future, while maintaining the ecological, environmental, and hydrological integrity [11]. The definition of water sustainability urges water resource managers to consider every impact of water-related programs and requires them to make difficult decisions regarding the selection, maintenance, and treatment of water sources in light of the increasing scarcity and prevalence of contamination in both surface water and groundwater [12]. Therefore, a comprehensive assessment that combines environmental, economic, and social criteria has become a high priority for sustainable water resource management to cope with complex and uncertain water-related issues [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The main objectives are to ensure that water resource systems are designed and managed to fully contribute to providing water of sufficient quantity and quality for agricultural, industrial, and municipal uses to meet the growing demands posed by social economic development, both now and in the future, while maintaining the ecological, environmental, and hydrological integrity [11]. The definition of water sustainability urges water resource managers to consider every impact of water-related programs and requires them to make difficult decisions regarding the selection, maintenance, and treatment of water sources in light of the increasing scarcity and prevalence of contamination in both surface water and groundwater [12]. Therefore, a comprehensive assessment that combines environmental, economic, and social criteria has become a high priority for sustainable water resource management to cope with complex and uncertain water-related issues [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated how uncertain HZ properties result in incorrect discharge calculations (e.g., Shanafield et al, 2011), with the Bayesian framework presented in this study, uncertainties in HZ properties are accounted for on flux estimates in a way that is transparent and coherent. Another application of such framework is goal-oriented campaign design, where field campaigns are optimized so that they maximize the expected data worth (e.g., Nowak et al, 2012;Harken et al, 2019). For example, if the goal of a given campaign is to estimate hydraulic conductivity, one should favor field measurements collected in high-flow conditions (e.g., winter) over low-flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater models have been used for decades in physically based risk assessments and as decision support tools for various applications (Freeze et al, 1990; Harken et al, 2019; Rajabi et al, 2018). To date, the majority of the subsurface modeling studies within the UD context have focused on the vertical migration of fracking fluids and formation brines from the deep target shale units to shallow aquifers.…”
Section: Introductionmentioning
confidence: 99%